Construction and Demolition Waste in Road Construction - Aditya Kumar Tiwary, Sandeep Nasier, Puneet Sharma (International Journal of Advanced Science and Technology, 2020)
Construction waste management is a very significant prudent and ecological arrangement for our societies. The huge amount of development and demolition waste (C&DW) with fast urbanization, development of economy and population, has put incredible weight on the limited landfill space. With quick urbanization the quantum of C&D waste is ever expanding and needs dire consideration. Our project focuses on conducting experiments with different compositions of C&D waste. We conducted experiments like Proctor test, CBR (Soaked and Unsoaked), UCS etc. We compared the results obtained from all these experiments with the standard material and calculated the optimum replacement of black cotton soil with recycled waste.